Pengaruh Model Pembelajaran Learning Cycle 7E Berbantuan Simulasi PhET untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Usaha dan Energi - Fazira Aflahunnisa Wigena; Parlindungan Sinaga; Dedi Sasmita (Mataram University, 2026)
Students’ critical thinking skills remain relatively low, particularly in physics learning, due to instructional processes that have not fully encouraged active student engagement. This study aimed to analyze the improvement of students’ critical thinking skills through the implementation of the Learning Cycle 7E model supported by PhET simulations. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design involving 31 students in the experimental class and 29 students in the control class. Data were collected using a critical thinking skills test and analyzed using IBM SPSS Statistics 31 through N-Gain, normality, homogeneity, Mann-Whitney, and effect size tests. The results showed that the experimental class obtained an N-Gain score of 0.71 in the high category, while the control class obtained 0.56 in the moderate category. The hypothesis test produced a significance value of < 0.001, indicating a significant difference between the two groups. In addition, the effect size value of 1.28 was categorized as high, indicating a strong effect of the treatment. These findings indicate that the Learning Cycle 7E model supported by PhET simulations is effective in improving students’ critical thinking skills.